Perturbaciones generadas en el sistema por generación Eólica - Pico Jiménez, Jeyson Alexander (2023)
In the present work, the wind generation system and its difficulty to stabilize the electrical system were analyzed, due to the uncertainty of the primary resource (wind), its acquisition occurs in places of difficult access, due to priority conditions for its correct performance as : speed and stability of the fluid, for which a robust infrastructure, both external and internal, is essential to be able to capture and transport electrical energy, knowing that the wind is a variable resource which can destabilize the parameters of the Electrical Power System (SEP), the aforementioned system uses power electronics, which injects harmonics, which can cause distortion in the frequency wave and voltage fluctuations, methods are determined to reduce these disturbances so that they do not affect the quality of the product using simulation programs, thus maintaining energy quality standards in the Electric Power System (SEP).